Servant Leadership Competence to Improve the Quality of Services for Health Workers Graduates of the Akademi Kesehatan John Paul II Pekanbaru - Anna Maria (PT FORMOSA CENDEKIA GLOBAL, 2023)
Leadership is a person's ability to influence others. Leadership competency is required in doing work. Servant leadership is one of the competencies that medical laboratory technologies must possess in serving laboratory visitors. Therefore, this service chose